2021
DOI: 10.3390/jcm10040835
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus and Infant Adiposity at Birth: A Systematic Review and Meta-Analysis of Therapeutic Interventions

Abstract: Exposure to untreated gestational diabetes mellitus (GDM) in utero increases the risk of obesity and type 2 diabetes in adulthood, and increased adiposity in GDM-exposed infants is suggested as a plausible mediator of this increased risk of later-life metabolic disorders. Evidence is equivocal regarding the impact of good glycaemic control in GDM mothers on infant adiposity at birth. We systematically reviewed studies reporting fat mass (FM), percent fat mass (%FM) and skinfold thicknesses (SFT) at birth in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 61 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…Although a potential mechanism linking HKDC1 to lipid metabolism was not proposed, the HAPO GWAS study also found a nominal association between HKDC1 variant rs4746822 and the number of skinfolds in neonatesa common way to quantify body fat in neonates and young infants [28]. Because increases in neonatal adiposity have been described in infants exposed to uncontrolled GDM in utero, this study indirectly links HKDC1 to a glucometabolic role [29,30]. Taken altogether, genetic studies have begun to reveal the role of HKDC1 in metabolism and human disease.…”
Section: Small Intestinementioning
confidence: 70%
“…Although a potential mechanism linking HKDC1 to lipid metabolism was not proposed, the HAPO GWAS study also found a nominal association between HKDC1 variant rs4746822 and the number of skinfolds in neonatesa common way to quantify body fat in neonates and young infants [28]. Because increases in neonatal adiposity have been described in infants exposed to uncontrolled GDM in utero, this study indirectly links HKDC1 to a glucometabolic role [29,30]. Taken altogether, genetic studies have begun to reveal the role of HKDC1 in metabolism and human disease.…”
Section: Small Intestinementioning
confidence: 70%
“…The incidence of cardiovascular events in women on MTF has been found to be lower to that of men on MTF. Despite some promising results with MTF regarding pregnancy rates in women with PCOS, for the management of gestational diabetes, cancer prevention or adjunctive cancer treatment and COVID-19, data from the most robust meta-analyses of clinical studies have yet to confirm such beneficial effects [ 35 , 38 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ]. A caveat is that any extrapolation of benefit to humans from animal or in vitro studies has to take into account the level of MTF concentration attained; the latter may differ considerably and be lower in humans [ 147 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 Specifically, while there is a clear link between GDM and delivery of infants that are large for gestational age (LGA), increased adiposity is also seen in the offspring of women with GDM and optimal glycemic control. 49 In addition, neonatal percent body fat does not correlate with maternal glucose levels in offspring of women with GDM. 50 Women with obesity without GDM, who are known to have increased circulating triglyceride but not glucose levels, give birth to offspring with increased adiposity.…”
Section: Lipid Handling In Utero and Early Offspring Steatosis Develo...mentioning
confidence: 97%